Global gyrokinetic turbulence simulations of MAST plasmas - Saarelma, S; Hill, P; Bottino, A; Colyer, G; Field, A; McMillan, B; Peeters, A; Roach, C; Team, MAST (2012)
Electrostatic gyrokinetic analyses are presented for an L-mode discharge with an internal transport barrier, from the spherical tokamak, MAST. Local and global microstability analysis finds similar linear growth rates for ion temperature gradient (ITG) driven modes. When the electron response is assumed to be adiabatic, growth rates are found to be lower than the experimental E×B flow shearing rate. Including kinetic electrons, without collisions, increases the ITG growth rates above the flow shearing rate, and these modes are found to be linearly unstable in the outer part of the plasma only. In global simulations the flow shear stabilization is found to be asymmetric with respect to the direction of the flow: there is a small destabilizing effect at low flow shear when the flow is in the co-direction. Global non-linear simulations with kinetic electrons and including the flow shear effects predict turbulent ion heat transport that is well above the neoclassical level in the region outside the internal transport barrier in this MAST plasma. In non-linear simulations we also find turbulence extending from the outer part of the plasma into the linearly stable core region. © 2012 IOP Publishing Ltd.